Is there a rise of the territorial dimension in the EU Cohesion Policy ? - Medeiros, Eduardo (2018)
This paper examines the role and importance of the territorial dimension of EU Cohesion Policy, during its five programming phases (1989‑2020), by relating this implementation process with several territorial elements, and by assessing their constant changes, namely in three main components and related elements: (i) the ‘policy strategy’ designed to include an integrated territorial perspective; (ii) the ‘policy impacts’ in territorial development and territorial cohesion, together with the use of territorial impact assessment procedures; and (iii) the focus on one or several ‘terri‑ torial scales’, specifically through the support to multilevel‑governance, territorial cooperation, and place‑based strategies. Paradoxically, despite the continuous attempts to detach EU Cohesion Policy from its initial goals of promoting a more cohesive Europe into a more neoliberalist paradigm type of ‘investment Policy’, our analysis showed that the territorial dimension is still very much anchored with this Policy, and even gaining importance in several territorial related elements, such as the support to territorial cooperation and governance processes, and the use of territorial impact assessment procedures.